Analisis Implementasi Customer Relationship Management dan Kualitas Pelayanan Jasa terhadap Kepuasan Pelanggan dan Dampaknya pada Retensi Pelanggan Hotel Bidakara Jakarta - Dian Tauriana; Ni Made Dini Arisani (Bina Nusantara University, 2012)
As the development of the business industry, it is now seen some companies that have a lot of customers so that it is required a good Customer Relationship Management to maintain long-term relationships with customers. Bidakara Hotel Jakarta is one of the services in the hospitality industry which implements Customer Relationship Management. Intense competition in the hospitality industry, Hotel Bidakara Jakarta must also consider the quality of care services to keep their customers satisfied and not switch to competitors through Customer Retention Strategy. In this study the author examines the influence and relationship between Customer Relationship Management and Service Quality on Customer Satisfaction and services impact on Customer Retention using Path Analysis. The results of this study show that the Customer Relationship Management Bidakara Hotel Jakarta is not contributing to the customers satisfaction. Quality services have positive and significant contribution to customers satisfaction; 'strong' influence. Customer Relationship Management has positive and significant contribution to the Customer Retention Bidakara Hotel Jakarta; 'weak' influence. Quality service has positive and significant contribution to the Customer Retention Bidakara Hotel Jakarta; 'strong' influence.